Keys for reading the Apocalypse of St. John - Gutiérrez Velasco, Flavio (2012)
This article proposes some reading keys to properly interpret the message of this controversial issue over the proliferation of fundamentalist readings of John’s Apocalypse, where we see the end of the world as imminent, such as the understanding of the apocalyptic genre that intended to strengthen Christian people persecuted during the Diocletian’s persecution in the late first century, or the same literary structure of the book that is focused on the number seven. Thus,this article is placed in line with the theology of history, an overview of the church history persecuted by the Romans in the late first century.